Microleakage of Two Bulk Fill and One Conventional Composite in Class II Restorations of Primary Posterior Teeth - Shahram Mosharrafian; Ali Reza Heidari; Pegah Rahbar (Tehran University of Medical Sciences, 2017)
Objectives: This study aimed to assess and compare the microleakage of two bulk fill and one conventional composite in class II restorations of primary posterior teeth. Materials and Methods: This in vitro, experimental study was conducted on 60 primary mandibular second molars, which were randomly divided into three groups. Standard class II cavities were prepared in teeth and restored with 3M bulk fill composite in group 1, SonicFill bulk fill composite in group 2 and Z250 conventional composite in group 3. Single Bond 2 bonding agent was used in all cavities. The teeth were then thermocycled and immersed in 1M silver nitrate solution. The teeth were then mesiodistally sectioned and evaluated under a stereomicroscope at´10 magnification. Dye penetration depth was recorded in microns and data were analyzed using one-way ANOVA. Results: The mean (± standard deviation) dye penetration depth in the gingival margins was 543±523µm, 343±290µm and 597±590µm for 3M bulk fill, SonicFill and Z250 conventional composite, respectively. These values were 214±93µm, 302±127µm and 199±145µm in the occlusal margins, respectively. The three groups were not significantly different in terms of occlusal or gingival microleakage (P>0.05), but gingival margins showed significantly higher microleakage than occlusal margins in all three groups (P<0.05). Conclusions: Bulk fill composites are not significantly different from conventional composites in terms of microleakage.